Estrategias integradas para la seguridad y protección de datos en la movilización marítima de contenedores de la terminal portuaria de Guayaquil - Sanunga Huaraca, Jorge Hernán (2025)
Maritime container mobilization plays a crucial role in international trade and Ecuador's economy, with the Guayaquil Port Terminal serving as a key hub. However, this port faces critical security challenges, particularly related to drug trafficking and money laundering. The main objective of this research was to develop integrated strategies to enhance security and data protection at the terminal to reduce contamination with regulated substances. A qualitative approach was adopted, utilizing a non-experimental descriptive and exploratory design. Methods included document analysis, interviews, and surveys of key personnel at the terminal. The results revealed significant deficiencies in current security procedures, as well as a lack of effective coordination among the different entities involved and the insufficiency of advanced technologies for inspection and control. The research concludes that it is essential to combine advanced technology, continuous training, and more effective cooperation among institutions to strengthen container security at the Guayaquil Port Terminal. These measures are crucial not only for improving operational efficiency but also for ensuring compliance with international regulations and protecting the national economy.